Design-based methodological advances to support national forest inventories: a review of recent proposals - Fattorini L (iForest - Biogeosciences and Forestry, 2015)
The aim of this paper is to give an overview of some recent proposals to support national forest inventories. The reviewed literature is strictly of design- based nature, i.e., uncertainty only stems from the sampling scheme actually adopted in the survey, rather than being assumed or modeled as in model- based approaches. National forest inventories are viewed as two-phase sample surveys to estimate at the same occasion the extent of the continuous population of points constituting the forest cover and the total of a forest attribute (e.g., volume or biomass) in the discrete population of trees for several forest types and/or administrative districts. The first phase is performed from remote sensing imagery while the second phase is performed on the field, possibly adopting the information acquired in the first phase as auxiliary information. A novel methodology is adopted based on Monte Carlo integration methods, which leads to a very general estimation strategy. Some recent proposals are considered in which remote sensing information acquired in the first phase is used to assess some physical characteristics of non-forest resources, such as woodlots, tree-rows and isolated trees outside the forest without additional field work. Finally, a new proposal is discussed in which canopy height from laser scanning is adopted as auxiliary information to recover missing data occurring when some sampled points cannot be reached because of hazardous terrain.